P453 Golimumab in real-world practice in patients with ulcerative colitis: 2-year interim results from a non-interventional trial in Germany. (25th January 2019) - Teich, N; Gruemmer, H; Joergensen, E; Liceni, T; Holtkamp-Endemann, W; Cornillie, F; Hohenberger, S; Fischer, T
Abstract: Background: Prospective data evaluating work productivity and activity in real-world practice are available in patients with moderate to severe ulcerative colitis (UC) treated with Golimumab (GLM) are rare. The aim of this study was to assess the change of work productivity, activity and quality of life (QoL) in UC patients treated with GLM for 2 years in an observational real-world setting in Germany. Methods: The WPAI-questionnaire (Work Productivity Activity Impairment Questionnaire) was used for the primary analysis. The change of work productivity and ability for daily activities at 3 months and 24 months vs. baseline visit was evaluated. The four subscores of WPAI were assessed: absenteeism, presenteeism, total work productivity impairment (TWPI), and activity impairment. Change in TWPI at Month 3 was the primary endpoint. To assess quality of life the IBDQ (Inflammatory Bowel Disease Questionnaire) and SF12v2 were used. Analysis population included all patients treated with GLM and who did have data for at least two visits ( n = 282). Results: A total of 287 UC patients were enrolled. Analysis population included 282 patients. Slightly less than half of the analysis population were male (47%). At baseline, 61% had moderate UC, 17% had severe UC by global physician's assessment. Concomitant steroids were used in 44% of patients. In total, 212 patients were analysed for the primary endpoint, as these were employed at baseline. 24 months after start of treatment all WPAI subscores showed significant improvements compared with baseline. Significant improvements were detected in the IBDQ and SF12v2 (Table 1). Conclusions: GLM treatment results in significant improvement of work productivity and daily activities in patients with UC up to 24 months after start of treatment. 1 Patients also experience a significant and clinically meaningful improvement in their QoL in terms of IBDQ 2 and SF12v2. 3 References 1. Wu JJ, Lin C, Sun L, et al. Minimal clinically important difference (MCID) for work productivity and activity impairment (WPAI) questionnaire in psoriasis patients. J Eur Acad Dermatol Venereol . 2018 doi:10.1111/jdv.15098. [Epub ahead of print] 2. Irvine et al . Gastroenterology 1994;2:287–296. 3. Drummond et al . Ann Med 2001;33:344–349.